Draft Annual Plan 2006-2007 Part-II Government of Sikkim - Planning Commission (Planning Commission, 2006)
The Planning and Development Department existed prior to the merger of Sikkim in 1975 with a Development Commissioner and limited staff strength With the joining in the mainstream, the development activities have increased and this Department has been redesignated as Development Planning, Economic Reforms and NEC Affairs Department in 2003.
Development Planning, Economic Reforms and North-Eastern Council Affairs Department, Government of Sikkim
Development Planning, Economic Reforms and North-Eastern Council Affairs Department, Government of Sikkim